Tazarotene cream in the treatment of psoriasis: Two multicenter, double-blind, randomized, vehicle-controlled studies of the safety and efficacy of tazarotene creams 0.05% and 0.1% applied once daily for 12 weeks - Weinstein, Gerald D.; Koo, John Y.M.; Krueger, Gerald G.; Lebwohl, Mark G.; Lowe, Nicholas J.; Menter, M.Alan; Lew-Kaya, Deborah A.; Sefton, John; Gibson, John R.; Walker, Patricia S. (Journal of the American Academy of Dermatology, 2003)
Background: Tazarotene in a gel formulation is widely used in the treatment of psoriasis. Objective: To determine the efficacy and safety of tazarotene 0.1% and 0.05% creams in the treatment of psoriasis. Methods: A total of 1303 patients participated in 2 clinical trials. Patients applied tazarotene creams 0.1% and 0.05% or vehicle once daily to all psoriatic lesions for 12 weeks followed by a 12-week posttreatment period. Results: Both creams were significantly more effective than vehicle on the basis of an overall assessment of psoriasis, a global response to treatment, and reduction in plaque elevation and scaling. Therapeutic effect was maintained during the posttreatment period. Common adverse events included signs and symptoms of skin irritation. Conclusion: Tazarotene creams were associated with significant reductions in the severity of the clinical signs of psoriasis and were found to be safe with acceptable tolerability. Tazarotene cream 0.1% was generally more effective, although slightly less well tolerated, than the 0.05% cream. (J Am Acad Dermatol 2003;48:760-7.)